Foreign Investment in Colombia's Financial Sector - Barajas, Adolfo; Salazar, Natalia; Steiner, Roberto (Washington, D.C. : International Monetary Fund, 1999)
This study analyzes foreign investment in Colombia's financial system, chronicling major changes in legislation, describing how investment flows evolved over time, and comparing performance of foreign-owned versus domestic banks. Panel data estimations reveal that financial liberalization in general had a beneficial impact on bank behavior in Colombia. Although the positive contribution of foreign entry may be overstated in recent studies by not controlling for other liberalization factors, foreign (and domestic) entry beginning in 1990 did improve bank behavior by enhancing operative efficiency and competition. However, this came at the expense of a deterioration in the loan quality of domestic banks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet